Microclimate Control in Strawberry Production with Hydroponic System in Indoor Vertical Farming - Edi Sugiyanto; Tota Pirdo Kasih (Jurnal Syntax Admiration, 2024)
The purpose of this paper is to analyze Microclimate Control in strawberry production using hydroponic system in Indoor Vertical Farming. This research will discuss the Microclimate parameters that affect strawberry growth to be controlled in maintaining strawberry productivity. The parameters controlled include temperature, humidity, CO2 levels, light and EC/pH of nutrients. The data collection technique of this research is taken using Priva Climate Computer technology whose settings are adjusted to the target parameters set and analyzed using the Priva Cloud Office Direct Client application which is part of the Priva Climate Computer technology. The results of the Microclimate control carried out, obtained temperature 17,8-20,9ºC, humidity 67,4-91,3%, Carbon Dioxide (CO2) levels 597-600 ppm, light with light intensity PPFD 29,9 μmol m-2s-1 and nutrient solution concentration with Electrical Conductivity (EC) 0,9-1,18 mS/cm and pH 5,8-6,1 in Indoor Vertical Farming. After going through a series of studies, the results of measuring environmental parameters are in accordance with the targets that have been set. It can be concluded that the results of the study are in accordance with the recommendations for environmental parameters for the growth of large and uniform strawberries. The results of this study can be used as a reference for readers to increase knowledge, practice commercial directly and become a reference for further research.